The Quantity and Quality of Humic Substances following Different Land Uses in Karst Peak-Cluster Depression in Guangxi, China - Tingting Cui; Jianbing Zhang; Weiqun Luo (Agriculture, 2023)
There were some ecological and environmental problems in limestone soil in the karst peak-cluster depression in Pingguo City of Guangxi, such as the destruction of soil structure, soil acidification and soil fertility decline, and these problems were closely related to soil organic matter. The soil in this site was classified as Cambisols. Therefore, this project took soil under five major land uses (grassland, afforestation, sugarcane field, corn field and pitaya field) in the karst area of Guangxi as the research object. The contents and molecular structure properties of humic acids, fulvic acids and humins in soils were studied by solid-state 13C nuclear magnetic resonance spectroscopy and elemental composition. From the perspective of the chemical structure of humic substances, the differences in the quantity and structural characteristics of humic acids, fulvic acids and humins in different land uses were revealed. The results showed that the organic carbon content of both afforestation (34.83 g kg−1) and natural restored grassland (31.67 g kg−1) were significantly higher than that of sugarcane field (17.60 g kg−1), corn field (16.35 g kg−1) and pitaya field (14.31 g kg−1) (p < 0.05). The contents of three humic fractions in grassland were relatively high, and the contents of three humic fractions in sugarcane field were relatively low (p < 0.05). The structural characteristics of humic substances showed that the protein components of the three humic fractions in the afforestation were high, indicating that the humic substances in the afforestation contained more unstable components. The Alkyl C/O-alkyl C and Hydrophobic C/hydrophilic C ratios of the three humic fractions of corn field were high, indicating high stability and maturity in humic substances in corn field.